Microcapsule type flame retardant, preparation method of microcapsule type flame retardant, composite phase-change material, preparation method of composite phase-change material and application of composite phase-change material

By using microcapsule flame retardant in the power battery module, the shell core is aluminum hypophosphate and the shell wall is melamine cyanurate, the problems of difficult heat dissipation and poor stability of aluminum hypophosphate are solved, and efficient flame retardant performance and battery safety are achieved.

CN119709132APending Publication Date: 2025-03-28GUANGDONG UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411816685.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The heat generated by the power battery module during charging and discharging is difficult to effectively dissipate, causing the battery to overheat, shorten its service life and may cause safety problems. Existing flame retardants such as aluminum hypophosphate have poor stability during processing and are difficult to widely use.

Method used

A microcapsule flame retardant is used, the shell core is aluminum hypophosphate and the shell wall is melamine cyanurate. The shell wall is self-assembled through hydrogen bonds to form the shell wall, wrap the shell core, delay its decomposition, and improve the flame retardant performance through the phosphorus-nitrogen synergistic flame retardant effect.

Benefits of technology

It effectively solves the problem of poor stability of aluminum hypophosphate during processing, improves the flame retardant performance of flame retardant, reduces the risk of thermal runaway, and ensures the safety and life of the battery module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709132A_ABST
    Figure CN119709132A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a microcapsule type flame retardant and a preparation method thereof, a composite phase change material and a preparation method and application thereof. According to the microcapsule type flame retardant provided by the invention, the melamine cyanurate is used for wrapping, aluminum hypophosphite can be isolated from a heat source, and decomposition of the aluminum hypophosphite is delayed, so that the problem of poor stability of the aluminum hypophosphite is effectively solved; the melamine cyanurate and the phosphorus-based flame retardant can also achieve a phosphorus-nitrogen synergistic flame retardant effect, so that the flame retardance of the flame retardant is improved. Furthermore, the invention also provides the composite phase change material, and the preparation raw materials comprise a phase change matrix, a supporting framework, a heat conduction reinforcing agent and a flame retardant, the flame retardant is ammonium polyphosphate and a microcapsule type flame retardant; when the composite phase change material is applied to a battery thermal management system, heat generated by a battery can be absorbed in time, the temperature of the battery is kept within a reasonable range, and when the battery is on fire abnormally, the composite phase change material can play a role in flame retardance and reduce the risk of thermal runaway.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a microcapsule-type flame retardant and a preparation method thereof, a composite phase change material and a preparation method and application thereof. Background Art

[0002] As the endurance of new energy electric vehicles continues to improve, the specifications and charge and discharge rates of power battery modules are also increasing, which brings new challenges to the development of new energy electric vehicles. Power battery modules release a lot of heat during the charging and discharging process. If this heat cannot be dissipated in a timely and effective manner, it will cause the battery to overheat. Overheating will not only accelerate the performance degradation of the power battery and significantly shorten its service life, but may also cause serious safety problems such as spontaneous combustion or explosion. Therefore, effective thermal management of power battery modules is one of the key factors to ensure the further development of new energy electric vehicles.

[0003] Among the many battery thermal management technologies, phase change material (PCM), as an emerging passive battery thermal management (BTM) technology, has attracted much attention due to its unique phase change process. During the phase change process, PCM can absorb or release a large amount of latent heat, absorb the heat generated by the battery in a timely manner and diffuse it into the surrounding environment, thereby stabilizing the internal temperature of the battery. Compared with traditional air-cooled and liquid-cooled BTM technologies, PCM has many significant advantages, including high energy storage density, small size, small temperature change, low cost, and easy matching with the operating system. For phase change materials, not only high thermal conductivity and large latent heat of phase change are required, but also excellent flame retardant properties are required.

[0004] Traditional flame retardants mainly include halogen-free phosphorus flame retardants, such as aluminum hypophosphite. However, aluminum hypophosphite has the problem of poor stability during processing. When the processing temperature is high or subjected to large shear stress, aluminum hypophosphite is easily decomposed and produces toxic and flammable phosphine gas, which greatly limits its promotion and application. Summary of the invention

[0005] The object of the present invention is to provide a microcapsule-type flame retardant and a preparation method thereof, a composite phase change material and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a microcapsule-type flame retardant, comprising a shell core and a shell wall wrapped on the surface of the shell core;

[0008] The shell core is aluminum hypophosphite;

[0009] The shell wall is melamine cyanurate; the melamine cyanurate is formed by self-assembly of melamine and cyanuric acid through hydrogen bonds.

[0010] Preferably, the mass percentage of the shell core in the microcapsule-type flame retardant is 50-80%, and the mass percentage of the shell wall is 20-50%;

[0011] The mass percentage of cyanuric acid in the melamine cyanurate is 40-60%, and the mass percentage of melamine is 40-60%.

[0012] The present invention also provides a method for preparing the microcapsule-type flame retardant described in the above technical solution, comprising the following steps:

[0013] Mixing cyanuric acid, aluminum hypophosphite and water to obtain a mixed solution;

[0014] Dissolving melamine in water to obtain a melamine solution;

[0015] The melamine solution is dripped into the mixed solution to carry out a self-assembly reaction to obtain the microcapsule-type flame retardant.

[0016] Preferably, the temperature of the self-assembly reaction is 70-110° C., and the time is 2-6 hours.

[0017] The present invention also provides a composite phase change material, the preparation raw materials include a phase change matrix, a support skeleton, a thermal conductivity enhancer and a flame retardant;

[0018] The flame retardant is ammonium polyphosphate and a microcapsule-type flame retardant; the microcapsule-type flame retardant is the microcapsule-type flame retardant described in the above technical solution or the microcapsule-type flame retardant prepared by the preparation method described in the above technical solution;

[0019] The support skeleton is obtained by reacting epoxy resin A and epoxy resin B.

[0020] Preferably, the phase change matrix comprises polyethylene glycol 2000;

[0021] The thermal conductivity enhancing agent includes expanded graphite.

[0022] Preferably, the mass percentage of each raw material in the composite phase change material is: phase change matrix 45-70%, support skeleton 10-20%, thermal conductivity enhancer 2-4%, ammonium polyphosphate 10-25%, microcapsule flame retardant 5-25%;

[0023] The mass ratio of epoxy resin A to epoxy resin B in the support skeleton is 1:1.

[0024] The present invention also provides a method for preparing the composite phase change material described in the above technical solution, comprising the following steps:

[0025] After the phase change matrix is ​​melted, epoxy resin A, ammonium polyphosphate and microcapsule flame retardant are sequentially added and first stirred to obtain a first mixture;

[0026] adding a thermal conductivity enhancer to the first mixture and performing a second stirring to obtain a second mixture;

[0027] The epoxy resin B is added into the second mixture to react and obtain the composite phase change material.

[0028] Preferably, the melting temperature is 90°C;

[0029] The first stirring speed is 700-1000 rad / min, and the time is 25-40 min;

[0030] The thermal conductivity enhancer is added to the first mixture in batches; the second stirring speed is 700-1000 rad / min, and the time is 20-30 min;

[0031] The reaction temperature is 60-70° C., the reaction time is 5 min, and the reaction is carried out under stirring at a stirring speed of 800 rad / min.

[0032] The present invention also provides the use of the composite phase change material described in the above technical solution or the composite phase change material prepared by the preparation method described in the above technical solution in battery thermal management.

[0033] The present invention provides a microcapsule flame retardant, comprising a shell core and a shell wall wrapped on the surface of the shell core; the shell core is aluminum hypophosphite; the shell wall is melamine cyanurate; the melamine cyanurate is formed by self-assembly of melamine and cyanuric acid through hydrogen bonds. The present invention uses melamine cyanurate for encapsulation, which can isolate aluminum hypophosphite from heat sources and delay its decomposition, thereby effectively solving the problem of poor stability of aluminum hypophosphite during processing. At the same time, melamine cyanurate is rich in nitrogen and produces a large amount of N2 when decomposed, which can dilute the concentration of oxygen and combustible gas, achieving a good flame retardant purpose. Melamine cyanurate and phosphorus flame retardant can also play a phosphorus-nitrogen synergistic flame retardant effect, further improving the flame retardancy of the flame retardant.

[0034] The present invention also provides a composite phase change material, the raw materials for preparation include a phase change matrix, a support skeleton, a thermal conductivity enhancer and a flame retardant; the flame retardant is ammonium polyphosphate and a microcapsule flame retardant; the microcapsule flame retardant is the microcapsule flame retardant described in the above technical solution or the microcapsule flame retardant prepared by the preparation method described in the above technical solution; the support skeleton is obtained by reacting epoxy resin A and epoxy resin B. The composite phase change material provided by the present invention adopts the APP-MAHP flame retardant system, so that the vertical combustion grade of the composite phase change material reaches V-0 level. When the composite phase change material is applied to the battery thermal management system, it can not only absorb the heat generated by the battery in time to keep the battery temperature within a reasonable range, but also play a flame retardant role when the battery catches fire abnormally, reducing the risk of thermal runaway. The composite phase change material provided by the present invention has excellent thermal stability and good heat storage and thermal conductivity. It is applied to battery thermal management technology, showing good temperature control ability of the battery module, ensuring that the battery is in a suitable operating temperature range, reflecting excellent application effects and broad market prospects.

[0035] The present invention also provides a method for preparing the composite phase change material described in the above technical solution, comprising the following steps: after melting the phase change matrix, adding epoxy resin A, ammonium polyphosphate and microcapsule flame retardant in sequence for a first stirring to obtain a first mixture; adding a thermal conductivity enhancer to the first mixture for a second stirring to obtain a second mixture; adding epoxy resin B to the second mixture for a reaction to obtain the composite phase change material. The preparation process provided by the present invention is simple, the time required is short, and the raw materials used are cheap and easy to obtain, and are environmentally friendly. No high temperature and high pressure or specific environmental atmosphere requirements are required during the reaction process, and mass production can be achieved, which has great potential for practical engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a DSC curve diagram of the composite phase change material obtained in Example 2;

[0037] Figure 2 is a graph showing the mass retention rate of the composite phase change material obtained in Example 2 after heating at 60° C. for 1 hour;

[0038] Figure 3 This is a schematic diagram of a shape stability test of the composite phase change material obtained in Example 2 when heated at 60° C. for 1 hour;

[0039] Figure 4 This is a UL-94 vertical combustion test diagram of the composite phase change material provided in Example 2;

[0040] Figure 5 This is a scanning electron microscope image of the composite phase change material obtained in Example 2;

[0041] Figure 6 This is a schematic diagram of the structure of a battery thermal management system containing the composite phase change material obtained in Example 2;

[0042] Figure 7 This is a battery temperature distribution diagram of a battery thermal management system containing the composite phase change material obtained in Example 2;

[0043] Figure 8 This is a diagram of the maximum temperature difference of a battery thermal management system containing the composite phase change material obtained in Example 2. DETAILED DESCRIPTION

[0044] The present invention provides a microcapsule-type flame retardant, comprising a shell core and a shell wall wrapped on the surface of the shell core;

[0045] The shell core is aluminum hypophosphite;

[0046] The shell wall is melamine cyanurate; the melamine cyanurate is formed by self-assembly of melamine and cyanuric acid through hydrogen bonds.

[0047] In the present invention, the shell core is aluminum hypophosphite (AHP). In the present invention, the mass percentage of the shell core in the microcapsule-type flame retardant is preferably 50-80%, specifically 50%, 60%, 70%, 80%. In the present invention, the aluminum hypophosphite is a halogen-free phosphorus flame retardant with a high phosphorus content and excellent flame retardant properties; by encapsulating it with melamine cyanurate, AHP can be isolated from heat sources and its decomposition can be delayed, thereby effectively solving the problem of poor stability of AHP during processing.

[0048] In the present invention, the shell wall is melamine cyanurate (MCA), and the melamine cyanurate is formed by self-assembly of melamine (MEL) and cyanuric acid (CA) through hydrogen bonding. In the present invention, the mass percentage of the shell wall in the microcapsule-type flame retardant is preferably 20-50%, specifically 20%, 30%, 40%, 50%. In the present invention, the mass percentage of cyanuric acid in the melamine cyanurate is preferably 40-60%, specifically 40%, 50%, 51%, 60%; the mass percentage of melamine is preferably 40-60%, specifically 40%, 49%, 50%, 60%. In the present invention, melamine cyanurate is a supramolecular material flame retardant formed by melamine and cyanuric acid through large-scale hydrogen bond self-assembly effect; MCA is rich in nitrogen and produces a large amount of N2 when decomposed, which can dilute the concentration of oxygen and combustible gas to achieve good flame retardant purpose; MCA and phosphorus flame retardant can also play a phosphorus-nitrogen synergistic flame retardant effect, further improving the flame retardancy of the flame retardant.

[0049] The present invention also provides a method for preparing the microcapsule-type flame retardant described in the above technical solution, comprising the following steps:

[0050] Mixing cyanuric acid, aluminum hypophosphite and water to obtain a mixed solution;

[0051] Dissolving melamine in water to obtain a melamine solution;

[0052] The melamine solution is dripped into the mixed solution to carry out a self-assembly reaction to obtain the microcapsule-type flame retardant.

[0053] The invention mixes cyanuric acid, aluminum hypophosphite and water to obtain a mixed solution.

[0054] In the present invention, the water is preferably deionized water. In the present invention, the mixing process preferably comprises: dissolving cyanuric acid in water, then adding aluminum hypophosphite, and continuing stirring.

[0055] In the present invention, the mass ratio of cyanuric acid to water is preferably 1:10. In the present invention, the dissolution temperature is preferably 90°C, the dissolution is carried out under stirring, and the stirring speed is preferably 700-1000 rad / min, more preferably 800 rad / min. In the present invention, the stirring time is preferably 2h.

[0056] The present invention dissolves melamine in water to obtain a melamine solution.

[0057] In the present invention, the water is preferably deionized water. In the present invention, the mass ratio of melamine to water is preferably 1:10.

[0058] After obtaining the melamine solution and the mixed solution, the present invention drips the melamine solution into the mixed solution to perform a self-assembly reaction to obtain the microcapsule-type flame retardant.

[0059] The present invention has no special limitation on the process of dripping, and the dripping is preferably carried out using a dropping funnel. In the present invention, the temperature of the self-assembly reaction is preferably 70-110°C, specifically 70°C, 80°C, 90°C, 100°C, 110°C, and the time is preferably 2-6h, specifically 2h, 3h, 4h, 5h, 6h; the time of the self-assembly reaction is the reaction time after the addition of materials is completed.

[0060] After the self-assembly reaction, the present invention also preferably includes filtering the obtained system while hot, washing the obtained precipitate with deionized water and drying it to obtain a white solid product, which is a microcapsule-type flame retardant.

[0061] The present invention also provides a composite phase change material, the preparation raw materials include a phase change matrix, a support skeleton, a thermal conductivity enhancer and a flame retardant;

[0062] The flame retardant is ammonium polyphosphate and a microcapsule-type flame retardant; the microcapsule-type flame retardant is the microcapsule-type flame retardant described in the above technical solution or the microcapsule-type flame retardant prepared by the preparation method described in the above technical solution;

[0063] The support skeleton is obtained by reacting epoxy resin A and epoxy resin B.

[0064] In the present invention, the phase change matrix preferably includes polyethylene glycol 2000 (PEG2000). In the present invention, the phase change matrix plays a role in providing latent heat of phase change; specifically, the phase change matrix is ​​the core component of the composite phase change material, and its main function is to provide latent heat of phase change. During the phase change process, the phase change matrix absorbs or releases a large amount of heat, thereby realizing energy storage or release. This characteristic makes the phase change matrix have important application value in temperature control and thermal management.

[0065] In the present invention, the thermal conductivity enhancer preferably includes expanded graphite (EG). In the present invention, the thermal conductivity enhancer plays a role in improving the thermal conductivity of the phase change polymer; specifically, the phase change material usually has a low thermal conductivity, which limits its application in rapid heat exchange. By adding the thermal conductivity enhancer, the thermal conductivity of the material can be significantly improved, so that heat is quickly conducted inside the material, thereby improving the phase change efficiency and response speed.

[0066] In the present invention, the support skeleton is obtained by reacting epoxy resin A (ER-A) and epoxy resin B (ER-B). In the present invention, the epoxy resin A is preferably a bisphenol A type epoxy resin, which has high adhesion and mechanical strength, and the specific model is E-51; the epoxy resin B is preferably a modified epoxy resin to provide better flexibility and impact resistance, and the specific model is E-20.

[0067] In the present invention, epoxy resin is used to construct a polymer network structure to provide mechanical support and fixed position for the phase change matrix. By forming a polymer network structure, the support skeleton can stabilize the phase change matrix in its position, prevent leakage during the phase change process, and ensure the stability and durability of the material.

[0068] In the present invention, the flame retardant is ammonium polyphosphate (APP) and microcapsule flame retardant (MAHP). In the present invention, the addition of flame retardant is to improve the safety of the material. Phase change materials may encounter high temperature or fire source during use, so they need to have good flame retardant properties. Flame retardant can form a protective layer on the surface of the material to prevent the spread of flames and ensure the safety of the material in high temperature environments. Specifically: After APP is introduced into the flame retardant system, APP and MAHP work synergistically to exert a dual flame retardant effect of gas phase and condensed phase, significantly inhibit the generation of combustible gases, and form a highly stable protective layer on the surface of the material, further insulating and oxygen-isolating. During the flame retardant process, the thermal decomposition of MAHP and APP not only generates phosphorus-containing compounds, effectively reducing the concentration of reactive free radicals in the flame zone, but also generates a large amount of nitrogen (N2). These non-combustible gases can dilute the oxygen and combustible gases in the combustion area, thereby inhibiting the spread of flames and improving the flame retardant properties and self-extinguishing ability of CPCM. This gas phase flame retardant effect is combined with the action of phosphoric acid produced by the pyrolysis of APP and AHP. Phosphoric acid promotes the dehydration and carbonization of the CPCM surface, forming a stable carbonized protective layer. In addition, the liquid film formed by phosphoric acid on the surface of the matrix can further protect the CPCM matrix from high temperature damage. In short, the synergistic effect of MAHP and APP forms a dual flame retardant mechanism of gas phase and condensed phase. This multi-level flame retardant strategy gives CPCM significant flame retardant advantages, making it have broad prospects in the field of high-efficiency flame retardant applications. MCA encapsulation of AHP helps to enhance the heat resistance and stability of the material, while APP further enhances the carbonization ability of the material and the formation effect of the protective layer. This synergistic effect can effectively improve the flame retardant properties of composite phase change materials.

[0069] In the present invention, the mass percentage of each raw material in the composite phase change material is preferably: phase change matrix 45-70%, support skeleton 10-20%, thermal conductivity enhancer 2-4%, ammonium polyphosphate 10-25%, microcapsule flame retardant 5-25%, and further preferably: phase change matrix 57%, support skeleton 15%, thermal conductivity enhancer 3%, ammonium polyphosphate 20%, microcapsule flame retardant 5%. In the present invention, the mass ratio of epoxy resin A and epoxy resin B in the support skeleton is preferably 1:1.

[0070] The present invention also provides a method for preparing the composite phase change material described in the above technical solution, comprising the following steps:

[0071] After the phase change matrix is ​​melted, epoxy resin A, ammonium polyphosphate and microcapsule flame retardant are sequentially added and first stirred to obtain a first mixture;

[0072] adding a thermal conductivity enhancer to the first mixture and performing a second stirring to obtain a second mixture;

[0073] The epoxy resin B is added into the second mixture to react and obtain the composite phase change material.

[0074] In the present invention, after the phase change matrix is ​​melted, epoxy resin A, ammonium polyphosphate and microcapsule flame retardant are added in sequence for first stirring to obtain a first mixture.

[0075] In the present invention, the melting temperature is preferably 90°C, and the melting is preferably carried out in a constant temperature oil bath. In the present invention, the first stirring speed is preferably 700-1000 rad / min, more preferably 800 rad / min; the time is preferably 25-40 min, more preferably 30 min.

[0076] After obtaining the first mixture, the present invention adds a thermal conductivity enhancer into the first mixture and performs a second stirring to obtain a second mixture.

[0077] In the present invention, the thermal conductivity enhancer is preferably added to the first mixture in batches, and the dispersion uniformity of the thermal conductivity enhancer can be further improved by adding in batches; the speed of the second stirring is preferably 700 to 1000 rad / min, more preferably 800 rad / min; the time is preferably 20 to 30 minutes. In the present invention, the temperature of the second stirring is preferably 90°C.

[0078] After obtaining the second mixture, the present invention adds epoxy resin B into the second mixture to react and obtain the composite phase change material.

[0079] In the present invention, before the epoxy resin B is added, the second mixture is preferably cooled to the temperature of the subsequent reaction. In the present invention, the reaction temperature is preferably 60-70°C, more preferably 65°C; the time is preferably 5 minutes, and the reaction is carried out under stirring, and the stirring speed is preferably 800rad / min. After the reaction, the present invention also preferably includes pouring the obtained liquid into a specific mold, and demolding after natural cooling.

[0080] The preparation method provided by the present invention can rapidly prepare composite phase change materials in large quantities. The raw materials used are simple and easy to obtain, low in cost, non-toxic and environmentally friendly, the preparation process has low equipment requirements, and does not require high temperature and high pressure. Compared with other inventions in the field of phase change polymers, it can achieve rapid and controllable batch preparation and has great practical application potential.

[0081] The present invention also provides the use of the composite phase change material described in the above technical solution or the composite phase change material prepared by the preparation method described in the above technical solution in battery thermal management.

[0082] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0083] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0084] Example 1

[0085] 15 g of cyanuric acid (CA) was added to a beaker, and 150 g of deionized water was added, and the mixture was stirred at 90°C and 800 rad / min to completely dissolve the mixture; 70 g of AHP was added to the beaker, and the mixture was stirred for 2 h to obtain a mixed solution;

[0086] 15 g of melamine (MEL) was dissolved in 150 g of deionized water to obtain a melamine solution;

[0087] The melamine solution was added dropwise into the mixed solution using a dropping funnel. After the addition was completed, the mixture was reacted at 90° C. for 4 hours. The mixture was filtered while hot, washed with deionized water, and dried to obtain a white solid product, which was recorded as microcapsule flame retardant (MAHP).

[0088] Example 2

[0089] 57 g of PEG2000 was weighed and poured into a constant temperature oil bath at 90° C. After the PEG2000 was completely melted, 7.5 g of ER-A (specifically bisphenol A epoxy resin, model E-51), 20 g of APP and 5 g of MAHP obtained in Example 1 were added in sequence, and mechanical stirring was used at a speed of 800 rad / min until the mixed material was completely melted to obtain a first mixture;

[0090] Weigh 3 g of expanded graphite, slowly add it to the first mixture in batches, and slowly increase the speed of mechanical stirring. After the expanded graphite is completely added, stir at a speed of 800 rad / min for 30 min until the expanded graphite is evenly dispersed, to obtain a second mixture;

[0091] The temperature of the second mixture was lowered to 65° C., 7.5 g of ER-B (specifically modified epoxy resin, specific model: E-20) was added, and the mixture was stirred at a speed of 800 rad / min for 5 min. The obtained mixture was poured into a specific mold, cooled naturally, and demolded to obtain a composite phase change material;

[0092] Among them, PEG2000 accounts for 57% of the total mass, ER accounts for 15% of the total mass, APP accounts for 20% of the total mass, MAHP accounts for 5% of the total mass, and expanded graphite accounts for 3% of the total mass.

[0093] Performance Testing

[0094] Test Example 1

[0095] The composite phase change material obtained in Example 2 was tested for anti-leakage and anti-deformation properties, and the test results obtained are as follows: Figures 1 to 3 As shown, Figure 1 is a DSC curve diagram of the composite phase change material obtained in Example 2;

[0096] Figure 2 is a graph showing the mass retention rate of the composite phase change material obtained in Example 2 after heating at 60° C. for 1 hour;

[0097] Figure 3 This is a schematic diagram of a shape stability test of the composite phase change material obtained in Example 2 when heated at 60° C. for 1 hour;

[0098] It can be seen from these test results that the latent heat value of the composite phase change material of Example 2 is 100.78 J / g, which shows that it can absorb this excess heat and use its latent heat effect to "store" the heat in the phase change process, thereby effectively alleviating the sharp fluctuations in battery temperature. After heating at 60°C for 1 hour, the mass retention rate of the composite phase change material was 99.41%, and the shape remained unchanged. Observing the filter paper on which the sample was padded, there was almost no leakage trace, which shows that the composite phase change material provided by the present invention has almost no leakage loss during the heating process, reflecting the excellent anti-leakage performance and shape stability of the phase change composite material under heating. Therefore, the material has excellent anti-leakage and anti-deformation properties, and can solve the problems of easy leakage and module deformation of phase change materials in existing battery thermal safety systems. The above-mentioned composite phase change material is applied to the thermal management of batteries. This thermal management method can not only improve the working efficiency of the battery, reduce the loss caused by overheating, but also extend the service life of the battery.

[0099] Test Example 2

[0100] In order to intuitively demonstrate the flame retardant properties of the composite phase change material, a vertical combustion test was conducted on the composite phase change material obtained in Example 2, and the test results and photos of the combustion process were recorded; Figure 4 This is a UL-94 vertical combustion test diagram of the composite phase change material provided in Example 2;

[0101] It can be seen that the first ignition is self-extinguished, and after the second ignition, the secondary ignition is self-extinguished, and no droplets fall. The results show that during the combustion process of the composite phase change material, a solid carbon layer quickly forms on the surface, which plays a role in preventing heat transfer and isolating oxygen.

[0102] Test Example 3

[0103] The microstructure and surface structure of the composite phase change material of Example 2 were observed using a scanning electron microscope at an accelerating voltage of 20 kV. Figure 5 This is a scanning electron microscope image of the composite phase change material obtained in Example 2;

[0104] The surface morphology of AHP and MAHP was observed from the microscopic perspective. Figure 5 In (a), the AHP particles present a more irregular and rough surface, and some particles show an angular morphology. Figure 5 The smoother surface of MAHP in (b) indicates the successful formation of the coating layer. This layer is formed by hydrogen bonding between cyanuric acid and melamine, providing a more uniform coating. Melamine cyanurate (MCA) is used as the shell wall to make microcapsules. In this way, AHP can be isolated from the heat source and its decomposition can be delayed, thus effectively solving the problem of poor stability of AHP during processing.

[0105] Test Example 4

[0106] A battery thermal safety system is provided, comprising a battery module containing the composite phase change material obtained in Example 2; the battery module is embedded in the composite phase change material and wrapped therein; Figure 6 This is a schematic diagram of the structure of a battery thermal management system containing the composite phase change material obtained in Example 2;

[0107] The battery uses the commercially available Lishen power battery LP2468134SA-23Ah, with a nominal capacity of 23Ah and a nominal voltage of 3.2V. In order to configure the battery module, the single battery is first charged and discharged by the charging and discharging equipment to screen out batteries with the same capacity. In addition, the single battery is welded and assembled into a battery module in the form of 2 (series) * 3 (parallel). The CPCM and the battery cell are the same in height and width. In order to ensure the phase change heat storage performance and minimize the contact thermal resistance, a flat and complete surface must be maintained on the CPCM board so that it fits tightly with the battery.

[0108] Figure 7 This is a battery temperature distribution diagram of a battery thermal management system containing the composite phase change material obtained in Example 2; Figure 8This is the maximum temperature difference diagram of the battery thermal management system containing the composite phase change material obtained in Example 2; it can be seen that at a discharge rate of 0.5C, the peak temperature is 38.41°C and the temperature difference is 2.12°C. At a discharge rate of 0.75C, the peak temperature is 42.92°C and the temperature difference is 3.26°C. At a discharge rate of 1C, the peak temperature is 47.51°C and the temperature difference is 4.23°C, showing a good thermal management effect. The results show that the battery module maintains a suitable maximum temperature and good temperature distribution during the charge and discharge cycle, ensuring that the battery module operates within a safe operating temperature range and exhibits optimal heat dissipation and heat distribution performance. Battery modules using high thermal conductivity and flame-retardant CPCM can effectively cope with the risk of thermal runaway and significantly improve the thermal management capabilities of electric vehicle battery systems.

[0109] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A microcapsule flame retardant, characterized in that: It comprises a shell core and a shell wall wrapped around the surface of the shell core; The shell core is aluminum hypophosphite; The shell wall is melamine cyanurate; the melamine cyanurate is formed by self-assembly of melamine and cyanuric acid through hydrogen bonds.

2. The microcapsule flame retardant according to claim 1, characterized in that: The mass percentage of the shell core in the microcapsule-type flame retardant is 50-80%, and the mass percentage of the shell wall is 20-50%; The mass percentage of cyanuric acid in the melamine cyanurate is 40-60%, and the mass percentage of melamine is 40-60%.

3. The method for preparing the microcapsule-type flame retardant according to claim 1 or 2, characterized in that: The following steps are involved: Mixing cyanuric acid, aluminum hypophosphite and water to obtain a mixed solution; Dissolving melamine in water to obtain a melamine solution; The melamine solution is dripped into the mixed solution to carry out a self-assembly reaction to obtain the microcapsule-type flame retardant.

4. The preparation method according to claim 3, characterized in that: The temperature of the self-assembly reaction is 70-110° C., and the time is 2-6 hours.

5. A composite phase change material, characterized in that: The preparation raw materials include a phase change matrix, a supporting skeleton, a thermal conductivity enhancer and a flame retardant; The flame retardant is ammonium polyphosphate and a microcapsule flame retardant; the microcapsule flame retardant is the microcapsule flame retardant according to claim 1 or 2 or the microcapsule flame retardant prepared by the preparation method according to claim 3 or 4; The support skeleton is obtained by reacting epoxy resin A and epoxy resin B.

6. The composite phase change material according to claim 5, characterized in that: The phase change matrix includes polyethylene glycol 2000; The thermal conductivity enhancing agent includes expanded graphite.

7. The composite phase change material according to claim 5 or 6, characterized in that: The mass percentage of each raw material in the composite phase change material is: phase change matrix 45-70%, support skeleton 10-20%, thermal conductivity enhancer 2-4%, ammonium polyphosphate 10-25%, microcapsule flame retardant 5-25%; The mass ratio of epoxy resin A to epoxy resin B in the support skeleton is 1:

1.

8. The method for preparing the composite phase change material according to any one of claims 5 to 7, characterized in that: The following steps are involved: After the phase change matrix is ​​melted, epoxy resin A, ammonium polyphosphate and microcapsule flame retardant are sequentially added and first stirred to obtain a first mixture; adding a thermal conductivity enhancer to the first mixture and performing a second stirring to obtain a second mixture; The epoxy resin B is added into the second mixture to react and obtain the composite phase change material.

9. The preparation method according to claim 8, characterized in that: The melting temperature is 90°C; The first stirring speed is 700-1000 rad / min, and the time is 25-40 min; The thermal conductivity enhancer is added to the first mixture in batches; the second stirring speed is 700-1000 rad / min, and the time is 20-30 min; The reaction temperature is 60-70° C., the reaction time is 5 min, and the reaction is carried out under stirring at a stirring speed of 800 rad / min.

10. Use of the composite phase change material according to any one of claims 5 to 7 or the composite phase change material prepared by the preparation method according to claim 8 or 9 in battery thermal management.

Citation Information

Cited By

  • Preparation method and application of melamine cyanuric acid coated phosphorus flame retardant

    CN120818184A

  • Preparation method and application of melamine cyanurate coated phosphorus-based flame retardant

    CN120818184B